Seismic Behavior of Steel Framed Structures with Infill Walls - Analytical Study - Akbaş, Elif Nazlı (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2017)
The objective of this numerical study was the investigation of the seismic behavior of steel framed structures with infill walls. The equivalent diagonal struts and shear spring model based finite element software SeismoStruct was employed for this purpose. The experimental test setup and the data obtained from the experiments were used to verify the two basic analytical models by using SeismoStruct software. Then, six new groups of frame models were formed by using the validated simple frame structures. The number of bays and stories were increased, and infill walls were introduced in alternative steel frames. The global structural performance parameters of top displacement, base shear, fundamental time period, out-of-plane displacement and local parameters of inter-story drift ratio and member deformation capacities were obtained for all models. These parameters were compared in each group of models to detect symmetry/asymmetry and vertical discontinuity based effects due to presence or absence of infill walls. From this study, it is concluded that infill walls can increase strength and stiffness of the systems depending on the location of them. Also, the orientation of vertical frame members have significant advantages such as decreased fundamental time period, zero-out-of-plane displacement for minor axis frame models.

ÖZ: Bu nümerik çalışma ile dolgu duvarların çelik çerçeve yapı sistemlerinin sismik davranışına etkileri araştırılmıştır. Bu amaç için çerçeve yapılardaki dolgu panellerin doğrusal olmayan davranışlarını modellemede eşdeğer basınç ve kesme çubuğu yaklaşımını esas alan sonlu elemanlar programı SeismoStruct kullanılmıştır. SeismoStruct kullanılarak referans olarak alınan bir deneysel çalışmanın yarı ölçekli örnekleri bilgisayar ortamında bire bir aynısı oluşturularak test edilmiştir. Daha sonra deneysel çalışmada kullanılan örneklerin açıklık ve kat sayıları artırılmış ve dolgu panellerin yerleri değiştirilerek altı adet yeni model grubu oluşturulmuştur. Bu modeller genel performans parametreleri olan yatay yer değiştirme, taban kesmesi, yapının serbest titreşim periyodu, düzlem dışı yer değiştirme ve lokal parametreler olan katlar arası rölatif deplasman ile eleman kapasiteleri açısından incelenmiştir. Dolgu duvarların varlığı ve simetrik/asimetrik yerleşimleri nedeniyle planda ve düşey düzlemde oluşan düzensizliklerin bu parametrelere etkisi her grup kendi içerisinde ve tüm gruplar karşılaştırılarak çıkarımlar yapılmıştır. Yapılan çalışma neticesinde dolgu duvarların konumuna bağlı olarak rijitlik ve sağlamlığı artırdığı sonucuna varılmıştır. Ayrıca, düşey taşıyıcı elemanların yerleşim yönlerinin yapının serbest titreşim periyodunu düşürmek ve düzlem dışı yer değiştirmeyi azaltmak gibi avantajları olduğu gözlemlenmiştir.
Master of Science in Civil Engineering. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Engineering, Dept. of Civil Engineering, 2017. Supervisor: Assoc. Prof. Dr. Mürüde Çelikağ.
Keywords: Civil Engineering; Building; Iron and steelxSteel; Structural; Structural stability; Steel frame; infill wall; infill panel; infilled steel frame; static-pushover analysis; moment frame